Implementasi Sistem GPS Tracker Berbasis IoT untuk Monitoring dan Tracking Tools Fiber Optik di PT XYZ - Ilmi, Nurul; Fathurahman, Mohamad (Spektral, 2025)
The development of modern communication technology demands fast and high-capacity data transmission, making fiber optics the primary choice in telecommunications infrastructure. The implementation of fiber optic technology requires special supporting devices such as splicers, Optical Time Domain Reflectometers (OTDRs), and Optical Power Meters (OPMs), which have high investment values ​​but are vulnerable to loss. PT XYZ, which is engaged in telecommunications infrastructure maintenance, experiences obstacles related to real-time location monitoring and limited visibility in managing high-value equipment assets. This study designs an Internet of Things (IoT)-based GPS tracker system for monitoring and tracking fiber optic equipment using the integration of the ESP32 architecture, SIM7600G-H module for 4G LTE connectivity, active GPS, and the Firebase Realtime Database. The monitoring website was developed with a role-based access control system that regulates three levels of access: Admin, Reviewer, and Field Team. The results of GPS accuracy testing at 11 locations in Jakarta showed an average deviation of 2.02 m with 90.9% of locations achieving the good to very good accuracy category (≤5 meters). The website's performance efficiency evaluation based on the ISO 25010 standard achieved a score of 90.20%, in the "Very Good" category, with a range of 88%-92%. The system is capable of providing real-time monitoring with update intervals of 30 seconds to 1 minute, minimizing the risk of asset loss and optimizing the efficiency of field fiber optic equipment management.